Digital Generation - Analysis of the Use of ICT by Young Poles (European Journal of Formal Sciences and Engineering, 2023)
In the Europe 2020 strategy in area of smart growth one of the flagship initiatives is Digital Agenda for Europe. Implementation of this initiative will lead to wide-availability of ICT solutions to society. Young people belonging to Generation Y most often treat the computer as a natural household equipment. Regular use of the Internet is very popular among them. They increasingly use mobile solutions in the field of ICT. The intelligent use of information technology possibilities will lead to sustainable economic growth. The purpose of the study was to cheque changes in the use of ICT among young Poles, and whether related behavioural patterns are similar in other countries of the European Union. The paper concludes with main reasons differencing generations in Poland due to the using the Internet.
Keywords: digital society, ICT, generations Y, X, BB, digital divide